2017
DOI: 10.1037/dhe0000013
|View full text |Cite
|
Sign up to set email alerts
|

Black male success in STEM: A case study of Morehouse College.

Abstract: The purpose of this study is to enhance our understanding of how a Historically Black College and University (HBCU) is cultivating Black male achievement in STEM. In this in-depth qualitative case study, we explore 2 resource-intensive and successful STEM pathway programs at Morehouse College, the only all-male HBCU in this country, as an opportunity to examine the cultivation of Black male STEM scholars. Our study was guided by 2 overarching questions: What opportunities for participation in a rigorous STEM e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Faculty mentoring of students is particularly important in the STEM disciplines because so much of student socialization is related to working closely with faculty in laboratories (Gasman, Nguyen, Conrad, Lundberg, & Commodore, 2017;Griffin et al, 2010;Palmer, Maramba, & Dancy, 2011). Administrators of diversity programs in STEM noted that faculty are often unwilling to collaborate and engage in diversity programming unless interest-convergence is present, where the faculty members identify a personal benefit to their participation (Baber, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Faculty mentoring of students is particularly important in the STEM disciplines because so much of student socialization is related to working closely with faculty in laboratories (Gasman, Nguyen, Conrad, Lundberg, & Commodore, 2017;Griffin et al, 2010;Palmer, Maramba, & Dancy, 2011). Administrators of diversity programs in STEM noted that faculty are often unwilling to collaborate and engage in diversity programming unless interest-convergence is present, where the faculty members identify a personal benefit to their participation (Baber, 2015).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Students who experienced positive mentoring relationships with faculty (and also postdoctoral scholars and graduate students) reported greater gains in STEM research skills (Ghee, Keels, Neal-Spence, & Baker, 2016). Scholarship also suggests that building a positive relationship with a mentor in the STEM disciplines may contribute to students' ability to see themselves as scientists (Gasman et al, 2017;James & Carlson, 2012). Developing an identity as a scientist starts early in an educational career (Pinkard, Erete, Martin, & McKinney de Royston, 2017) and can contribute to an individual's long-term persistence in a STEM field (Rodriguez & Lehman, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The intended course outcomes for the students included being able to demonstrate a more complex understanding of contemporary science and acquire the necessary skills to perform science at an advanced level with an interest in pursuing a STEM career. A key component to the scientific literacy course was the upper level student leaders who were there to support and challenge the students because mentorship has been known to be an effective part of student success in STEM [37,38]. Overall, the course was designed to deliver new information to students that will build upon their scientific literacy and retention in STEM.…”
Section: Course Curriculummentioning
confidence: 99%
“…These faculty relationships were imperative to increasing student retention and success among Black male collegians (Barker & Avery, 2012;Bonner, 2001;Brooms & Davis, 2017;Fischer, 2007;Fries-Britt, 2001;Gasman et al, 2017;Hotchkins & Dancy, 2015;Palmer et al, 2010). Students in the study also found support in the BMI Program…”
Section: Discussionmentioning
confidence: 99%